Synchronous macro-programming of energy-efficient wireless sensor-actuator networks . - Karpinski, Marcin (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2010)
Application development for wireless sensor-actuator networks (WSANs) is widely regarded as being a complex task: not only does the programmer need to orchestrate communication and data processing in a heterogeneous network of potentially resource-limited and unreliable devices, but he also needs to ensure timely operation of the system so that the temporal relationship between sensor readings and actuator stimuli is maintained. Macro-programming, originally proposed for the more general domain of wireless sensor networks (WSNs), is a programming paradigm in which applications are concisely specified using concepts whose semantics involve potentially large collections of network nodes, thus, significantly reducing the programming burden. However, macro-programming WSAN applications remains a largely unaddressed problem because the languages proposed to date have either focused on data transformations in the network while neglecting the temporal aspect of WSAN applications, or they do not offer any support for energy-efficient operation.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin.